Immunomediated Encephalitis: New Diagnoses on the Neurology–Psychiatry Interface - Daniel Damiani; Aline Ribeiro de Bem (Brazilian Neurosurgery)
Immune-mediated encephalitis is a real diagnostic challenge. Initially, patients present with subacute behavioral alterations, evolving over months, being attributed to purely psychiatric mechanisms, as well as neurological symptoms that often go unnoticed by professionals who are not neurologists. The etiologies behind these diseases are represented by paraneoplastic syndromes (including occult tumors) as well as viral infections, in both cases constituting true immunological triggers with exposure of antigens that will lead to a cross-immunological response directed at healthy structures of the nervous system. In the current review, we present the different clinical scenarios which differ based on antibodies against membrane receptors described so far, emphasizing the relevance of an early diagnosis for a smaller impact on prognosis.